2017
DOI: 10.1152/ajpheart.00003.2017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lymphangion chain length and maximum pressure generation established through in vivo imaging and computational modeling

Abstract: The intrinsic contraction of collecting lymphatic vessels serves as a pumping system to propel lymph against hydrostatic pressure gradients as it returns interstitial fluid to the venous circulation. In the present study, we proposed and validated that the maximum opposing outflow pressure along a chain of lymphangions at which flow can be achieved increases with the length of chain. Using minimally invasive near-infrared imaging to measure the effective pumping pressure at various locations in the rat tail, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
(107 reference statements)
2
15
0
1
Order By: Relevance
“…This was initially shown with measurements of pressures within lymphatic networks of exteriorized mesentery, which revealed that with each passage across a secondary valve to a downstream segment, intraluminal pressure increases gradually (415, 416, 1225). This concept was later confirmed in the rat tail with noninvasive near infrared imaging and computational modeling (892). Each step can be overcome by the phasic constriction of the lymphangion by its lymphatic smooth muscle layer.…”
Section: Lymphangions and The Lymphatic Pump Mechanismmentioning
confidence: 89%
“…This was initially shown with measurements of pressures within lymphatic networks of exteriorized mesentery, which revealed that with each passage across a secondary valve to a downstream segment, intraluminal pressure increases gradually (415, 416, 1225). This concept was later confirmed in the rat tail with noninvasive near infrared imaging and computational modeling (892). Each step can be overcome by the phasic constriction of the lymphangion by its lymphatic smooth muscle layer.…”
Section: Lymphangions and The Lymphatic Pump Mechanismmentioning
confidence: 89%
“…Mice that swell significantly at any timepoint have sustained dysfunction in pumping pressure even as swelling returns close to baseline levels. Previous work combining computational and experimental data has shown that pumping pressure is a measurement of force generation of lymphatic muscle cells 25 . Low pumping pressure has also been described in humans with leg lymphedema, suggesting that a loss of collecting vessel pressure generation is correlated with the swelling experienced during lymphedema 26 .…”
Section: Discussionmentioning
confidence: 99%
“…To compare differences in collagen organization, image stacks were collected in the valvular and tubular regions; the tubular region was defined as 100 µm distance from the valve. Note that a typical rat tail is 3.3 mm 37 . The image z-stacks were imported in ZEN lite (Zeiss, Inc.) software to obtain 3D reconstructions.…”
Section: Methodsmentioning
confidence: 99%